THE FEATURES OF THE PROCEDURE FOR MAKING THE DECISION ON THE IMPLEMENTATION OF PROJECTS THE PUBLIC-PRIVATE PARTNERSHIP - M. Vorobiova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2018)
The procedure for making a decision on the implementation of public-private partnership, which has developed in Ukraine was examined in the article. Three consecutive stages of preparation for the implementation of projects of partnership between the state and business were сomprehensively considered. The main disadvantages of each stage were determined and suggestions for their improvement were given.